2022
DOI: 10.1038/s41591-022-02100-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of wearable device-measured vigorous intermittent lifestyle physical activity with mortality

Abstract: Wearable devices can capture unexplored movement patterns such as brief bursts of vigorous intermittent lifestyle physical activity (VILPA) that is embedded into everyday life, rather than being done as leisure time exercise. Here, we examined the association of VILPA with all-cause, cardiovascular disease (CVD) and cancer mortality in 25,241 nonexercisers (mean age 61.8 years, 14,178 women/11,063 men) in the UK Biobank. Over an average follow-up of 6.9 years, during which 852 deaths occurred, VILPA was invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 52 publications
3
104
0
2
Order By: Relevance
“…Interestingly, Stamatakis et al proposed a new paradigm that allows VPA to be more accessible with the aid of the regular accumulation of vigorous intermittent lifestyle physical activity (VILPA) as part of daily living, such as carrying shopping bags and stair climbing [41]. They recently showed that 3 bouts per day (4.4 min per day) was associated with a reduction in all-cause, CVD and cancer mortality, whereby non-exercisers appeared to elicit beneficial health effects of similar magnitude to exercisers [42]. This emphasizes the potential of promoting VILPA No differences on cardiometabolic health related outcomes were found between groups, which was also confirmed by the multivariate regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Stamatakis et al proposed a new paradigm that allows VPA to be more accessible with the aid of the regular accumulation of vigorous intermittent lifestyle physical activity (VILPA) as part of daily living, such as carrying shopping bags and stair climbing [41]. They recently showed that 3 bouts per day (4.4 min per day) was associated with a reduction in all-cause, CVD and cancer mortality, whereby non-exercisers appeared to elicit beneficial health effects of similar magnitude to exercisers [42]. This emphasizes the potential of promoting VILPA No differences on cardiometabolic health related outcomes were found between groups, which was also confirmed by the multivariate regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to now easily detect health data will allow us to measure the effects of “easily to integrate into everyday life” physical activity. Just recently, it has been shown that three to four minutes of vigorous lifestyle physical activity (VILPA), such as very fast walking while commuting to work, is associated with lower all-cause CVD and cancer mortality risk [ 197 ]. Studies like this will help us to better comprehend “how little is enough” while still maximizing the beneficial effects of exercise.…”
Section: Future Directionsmentioning
confidence: 99%
“…115 Physical activity does not need to be accumulated all at once, with findings suggesting intermittent physical activity throughout the day is associated with reduced all-cause and CVD-related death. 116 This can be important for those employed in primarily sedentary occupations.…”
Section: Middle Adulthood (45-64 Years)mentioning
confidence: 99%